Blended learning (Ensino híbrido): a evasão na pós-graduação lato sensu - Santos, Alexandra Venancio dos (2020)
Courses in the blended learning model as a possibility for development in education have gained strength as a result of contemporary transformations related to technologies, however there is little research that evaluates these courses, mainly in relation to dropout rates. Therefore, the main objective of this study was to evaluate the phenomenon of evasion in the blended learning model, from a sample of 480 students and alumni of graduate courses in lato sensu at Saint Paul Escola de Negócios. Through multivariate binary logistic regression, six variables were tested in order to understand which factors are most relevant for predicting evasion. The results indicate that three continuous random variables are able to bring predictability as to evasion, being elapsed time, since about 60% of evasions occur with only 30% of the course time; average grade, reflecting students' difficulties; and time dedicated to the virtual learning environment (VLE). This research contributes to the reduction of dropout rates in hybrid education and, consequently, to improve the retention rates of students in postgraduate blended learning courses